A note on zoosporogenesis in Phytophthora colocasiae - MISRA, R.S. (Indian Phytopathology, 2002)
A brief report on zoosporangia morphology and germination of P. colocasiae (the causal agent of leaf blight in Colocasia esculenta and C. antiquorum) is given.